Pengaruh Karakteristik Individu, Karakteristik Pekerjaan dan Gaya Kepemimpinan terhadap Kepuasan Kerja dalam Meningkatkan Kinerja Pegawai - Adolfina, Wagey, Mandey, (Universitas Sam Ratulangi, 2018)
The results showed that 1) individual characteristics had a positive and significant effect on job satisfaction, 2) job characteristics had a positive and significant effect on job satisfaction, 3) leadership style had a positive and significant effect on job satisfaction, 4) individual characteristics directly influenced but not significant to employee performance, and indirectly through job satisfaction affect employee performance, 5) job characteristics directly or indirectly through job satisfaction, have a positive and significant effect on employee performance, 6) leadership style directly has a negative and insignificant effect on employee performance, but indirectly through job satisfaction affects employee performance, 7) job satisfaction has a positive and significant effect on employee performanceKeywords: Individual Characteristics, Job Characteristics, Leadership Style, Job Satisfaction, Employee Performance